The Concept of God According to Sa’id Nursi - Achmad Reza Hutama Al Faruqi; Rif’at Husnul Ma’afi; Filaila Nurfaiza (International Journal Ihya' 'Ulum al-Din, 2021)
The concept of God is a fundamental concept for every religion, especially Islam.  The concept of God in Islam is different from other religions, even emerging from the time of the Greek philosophical tradition and Eastern and Western mystical traditions.  Not a few Muslims state that all religions are the same God. This is a problem for the religions of this world.  Therefore, Sa’id Nursi clearly stated that the concept of God according to Islam is different from the concept of God according to other religions.  The method used by the writer is descriptive and analytical.  In this case, Badi'uzzaman has a perspective on the concept of God.  God, according to Badi'uzzaman, is one immanent and radiates his light into the universe, thus creating the greatness of the universe and its contents, which is often called Tauhīd.  Nursi understands monotheism as the basis of ideology and epistemology viewing the universe.  So, Nursi's concept of divinity emphasizes the monotheistic aspect, in contrast to the esoteric and exoteric sides.